Methodological considerations for survey research: Validity, reliability, and quantitative analysis - Mellinger, Christopher D.; Hanson, Thomas A. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
As translation and interpreting studies continue to develop cognitive theories of translator and interpreter behavior and processing, there has been increased emphasis on research methods and data collection methodologies to glean new insights into the translation process. This article presents a critical review of survey research methods in Cognitive Translation Studies and argues for their inclusion as a means of better understanding translator and interpreter attitudes, behaviors, perceptions, and values. The article begins with a reflection on measurement and the need for alignment with theoretical frameworks and constructs; then it reviews important considerations when developing theoretically-grounded, empirically-based survey instruments, namely, validity, reliability, measurement invariance, and quantitative analysis. The article concludes with a call for additional methodological reflection on developing and using survey instruments.